A note about the different characterizations of the expected utility theorem - Flores Zarur, Karla; Olvera López, William José; Plata Pérez, Leobardo (Estudios Económicos de El Colegio de México, 2022)
In this work, we prove the axiomatic equivalence of several characterizations of the Expected Utility Theorem proposed by Mas-Colell et al. (1995), Jehle and Reny (2011), Maschler et al. (2013), and Rubinstein (2012). A general language is used for unifying the notation, and we introduce a recursive definition of the lottery space in the expected utility theory.